Reduction Cost in Endplate-B Material Component for Oil Filter Bypass System with Redesigning - Satria, Adam; Sahrial Solih, Edwin; Putri Purbaningrum, Sanurya; Wahid Arohman, Abdul; Ridho Hans Gurning (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The bypass system in spin-on type oil filters plays a crucial role in maintaining engine cleanliness and performance by allowing oil to flow when excessive pressure occurs. A critical component of this system is endplate-B, which fulfills dual roles: providing structural support and functioning as an interface for oil passage during bypass operations. However, the relatively high material usage and cost associated with the current design of endplate-B pose challenges in manufacturing efficiency. The objective of this study is to minimize the material cost of endplate-B by optimizing its dimensional geometry without compromising its structural and functional performance. The research methodology encompasses dimensional redesign, structural analysis, and performance validation under simulated operating conditions. The findings indicate that strategic dimensional modifications can substantially reduce material usage while preserving mechanical strength and functional integrity. The implementation of this optimized design provides a cost-effective solution for the manufacturing of oil filters and contributes to broader efforts to improve production efficiency in the automotive component industry.